Electrically peelable adhesive composition, electrically peelable adhesive product and use thereof

Incorporating a superabsorbent polymer into an electrically releasable adhesive composition with an acrylic polymer and ionic liquid addresses the issue of deteriorating releasability at high temperatures, ensuring effective and residue-free peeling in demanding environments.

JP7602293B2Active Publication Date: 2024-12-18BIG TECHNOS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023579989
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-10
Publication Date
2024-12-18
Estimated Expiration
2042-02-10

AI Technical Summary

Technical Problem

Existing electrically releasable adhesives deteriorate in electrical releasability when exposed to high temperature environments for extended periods.

Method used

Incorporating a superabsorbent polymer into an electrically releasable adhesive composition containing an acrylic polymer and an ionic liquid to enhance heat resistance.

Benefits of technology

The adhesive composition maintains excellent electrical releasability even under high temperature conditions, allowing for effective peeling without residue, suitable for applications requiring durability and ease of removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602293000018
    Figure 0007602293000018
  • Figure 0007602293000019
    Figure 0007602293000019
  • Figure 0007602293000020
    Figure 0007602293000020
Patent Text Reader

Abstract

The present invention addresses the problem of providing an electrically peelable adhesive product which has excellent electrical peelability even under such conditions that the electrically peelable adhesive product is exposed to high temperatures for a long period of time. The problem is solved by an electrically peelable adhesive composition which contains an acrylic polymer, an ionic liquid and a superabsorbent polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrically releasing adhesive composition.The present invention relates to an electrically releasing adhesive product.The present invention relates to a method for removing an electrically releasing adhesive product. [Background technology]

[0002] Adhesives and adhesive tapes that have adhesion to and releasability from an adherend are used in various applications (for example, surface protection films, masking tapes for painting, peelable memos, etc.). As a method for peeling an adhesive from an adherend, in addition to physical methods, methods of peeling by stimuli such as light, heat, vibration, or electrical current are known. For example, Patent Document 1 describes that by using a polymer and an ionic liquid in the adhesive, an adhesive that can be peeled from an adherend by applying a voltage (electrically peelable adhesive) can be provided. In addition, Patent Document 2 describes that by examining the conditions of a transfer promoter used together with the polymer and the ionic liquid, an electrically peelable adhesive that does not leave any adhesive residue even when a low voltage is applied can be provided. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-037354 A [Patent Document 2] U.S. Patent Application 17 / 602,212 Summary of the Invention [Problem to be solved by the invention]

[0004] In the course of their research into electrically peelable adhesives, the inventors have found a new problem that the electrically peelable adhesive composition described in Patent Document 2 has excellent electrical peeling properties when used at room temperature, but the electrical peeling properties decrease when exposed to a high-temperature environment for a long period of time. Therefore, an object of the present invention is to provide an electrically peelable adhesive product that has excellent electrical peeling properties even when exposed to a high-temperature environment for a long period of time, in order to apply the electrically peelable adhesive to various products. [Means for solving the problem]

[0005] The inventors discovered that by adding a highly water-absorbent polymer to a conventional electrically peelable adhesive composition containing an acrylic polymer and an ionic liquid, it is possible to provide an electrically peelable adhesive product with excellent heat resistance, and thus arrived at the present invention. Therefore, the present invention provides an electrically releasing adhesive composition comprising an acrylic polymer, an ionic liquid and a highly water-absorbent polymer.

[0006] The present invention provides an electrically releasing adhesive product having a substrate and an electrically releasing adhesive layer formed in contact with the substrate, the electrically releasing adhesive layer comprising the above-mentioned electrically releasing adhesive composition. According to the present invention, there is provided an electrically peelable adhesive product having a core material and two electrically peelable adhesive layers formed so as to be in contact with both sides of the core material, the electrically peelable adhesive layers comprising the above-mentioned electrically peelable adhesive composition.

[0007] The present invention provides a method for peeling an electrically peelable adhesive product, which comprises attaching the above-mentioned electrically peelable adhesive product to a conductive object so that the adhesive layer is in contact with the conductive object, and then applying a voltage of 30 V or less to the adhesive layer via the conductive object, thereby peeling the adhesive product from the conductive object to which it is directly attached, wherein the conductive object is any one of a conductive adherend, a conductive auxiliary material, or a conductive object to be fixed. Effect of the Invention

[0008] According to the present invention, there is provided an electrically releasing pressure sensitive adhesive composition which exhibits excellent electrical releasing properties even when exposed to high temperature conditions. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows an example of a cross section of an electrically releasing adhesive product in the form of a single-sided tape. [Diagram 2] FIG. 1 shows an example of a cross-section of an electrically releasable adhesive product in the form of a double-sided tape. [Figure 3A] FIG. 1 is a diagram showing an example of a circuit for applying a voltage to a conductive adherend and a conductive substrate, and peeling the conductive substrate from an electrically peelable adhesive product. [Figure 3B] FIG. 13 is a diagram showing an example in which a conductive substrate is peeled off by applying a voltage. [Figure 4A] FIG. 1 is a diagram showing an example of a circuit in which a voltage is applied to a conductive adherend and a conductive object to be fixed, and the conductive object to be fixed is peeled off from an electrically peelable adhesive product. [Figure 4B] 13A and 13B are diagrams showing an example in which a conductive object to be fixed is peeled off by applying a voltage. [Figure 5A] FIG. 1 is a diagram showing an example of a circuit for peeling a non-conductive object to be attached from an electrically peelable adhesive product by applying a voltage to a conductive adherend and a conductive auxiliary material. [Figure 5B] 13A and 13B are diagrams showing an example in which a non-conductive object to be fixed is peeled off by applying a voltage. [Figure 6A] FIG. 13 is a diagram showing an example of a circuit for applying a voltage to a conductive auxiliary material and a conductive object to be attached, thereby peeling the conductive object to be attached from an electrically peelable adhesive product. [Figure 6B] 13A and 13B are diagrams showing an example in which a conductive object to be fixed is peeled off by applying a voltage. [Figure 7A] FIG. 1 is a diagram showing an example of a circuit in which a voltage is applied to a conductive auxiliary material adhered to a non-conductive adherend and a conductive auxiliary material adhered to a non-conductive object to be fixed, thereby peeling the non-conductive object from the electrically peelable adhesive product. [Figure 7B] 13A and 13B are diagrams showing an example in which a non-conductive object to be fixed is peeled off by applying a voltage. [Figure 8A] 1 is a simplified cross-sectional view of an evaluation sample. [Figure 8B] FIG. 1 is a simplified diagram of a pulling test. [Figure 8C] FIG. 1 is a simplified diagram of a pulling test. [Figure 9] FIG. 13 is a diagram showing the results of a pulling test after voltage application for evaluation samples of Comparative Example 1 and Examples 1 to 3 after a heating acceleration test. [Figure 10] FIG. 13 is a diagram showing the results of a pulling-up test after voltage application for the evaluation samples of Comparative Example 1, Example 1 or Example 2 after a heating acceleration test. [Figure 11] FIG. 13 is a diagram showing the results of a pulling test after voltage application for evaluation samples of Comparative Example 1 and Example 4 after a heating acceleration test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, "x to y" (x and y are specific values) means at least x and at most y, unless otherwise specified.

[0011] The acrylic polymer of the present embodiment can be obtained by polymerizing an acrylic monomer in the presence of any polymerization initiator. Any polymer can be used as the acrylic polymer as long as it can adhere to a conductive object. The conductive object refers to a conductive adherend, a conductive auxiliary, a conductive substrate, or a conductive object to be fixed (these definitions will be described later). From the viewpoint of adhesion, the weight average molecular weight of the acrylic polymer is preferably 100,000 to 5,000,000, more preferably 200,000 to 4,000,000, and more preferably 300,000 to 3,000,000. Here, the weight average molecular weight refers to the weight average molecular weight in terms of polystyrene. Specifically, it may be the weight average molecular weight in terms of polystyrene calculated using GPC (System21) by Shodex Co., Ltd., with tetrahydrofuran as the mobile phase.

[0012] The glass transition temperature (Tg) of the acrylic polymer is preferably not higher than 0° C., more preferably not higher than −20° C., and even more preferably not higher than −40° C. The Tg can be calculated, for example, based on the following Fox equation. 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+·····+(Wn / Tgn) The glass transition temperature can be measured, for example, by differential thermal analysis (DTA).

[0013] The acrylic polymer may be crosslinked by the action of a crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents such as toluene diisocyanate and methylene bisphenyl isocyanate. The amount of the crosslinking agent is preferably 1 to 10 parts by weight, more preferably 3 to 10 parts by weight, and more preferably 5 to 10 parts by weight, based on 100 parts by weight of the acrylic polymer. When the electrically peelable pressure-sensitive adhesive composition is formed as a layer on a substrate, crosslinking the acrylic polymer can improve the creep resistance and / or shear resistance of the layer.

[0014] The acrylic polymer more preferably contains a copolymer of an alkyl(meth)acrylate having an alkyl group having 1 to 8 carbon atoms, a carboxyl group-containing acrylic monomer, and / or a hydroxyl group-containing acrylic monomer. When the acrylic polymer contains such a copolymer, an electrically peelable pressure-sensitive adhesive composition having excellent adhesive strength is obtained.

[0015] (Acrylic Monomer) The acrylic monomer preferably contains, as a main component (50% by weight or more), an alkyl(meth)acrylate having an alkyl group with a carbon number of 1 to 14. Here, (meth)acrylate means methacrylate or acrylate.

[0016] Examples of alkyl (meth)acrylates having an alkyl group having 1 to 14 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, and dodecyl (meth)acrylate. These alkyl (meth)acrylates may be used alone or in combination of two or more. Among these alkyl (meth)acrylates, alkyl (meth)acrylates having an alkyl group having 1 to 8 carbon atoms are preferred, alkyl (meth)acrylates having an alkyl group having 1 to 4 carbon atoms are more preferred, n-butyl (meth)acrylate is more preferred, and n-butyl acrylate is more preferred.

[0017] Examples of the other acrylic monomers include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, and carboxyethyl acrylate, and hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate. These other acrylic monomers may be used alone or in combination of two or more. The other acrylic monomers preferably include either a carboxyl group-containing monomer or a hydroxyl group-containing monomer, or both.

[0018] The acrylic monomer may be composed only of alkyl (meth)acrylate without using the other acrylic monomers described above. From the viewpoint of easily obtaining an electrically peelable adhesive composition with the desired performance, the content of the other acrylic monomer is preferably 1% by weight or more and less than 50% by weight, more preferably 5 to 30% by weight, and even more preferably 5 to 15% by weight.

[0019] In addition, when either a carboxyl group-containing monomer or a hydroxyl group-containing monomer, or both, are contained, the total content of these two monomers is not particularly limited, but is preferably in the range of 1 to 20 parts by weight when the total monomer amount is 100 parts by weight. By using both monomers in this range, the adhesive properties can be improved. Furthermore, the total content of both monomers is more preferably in the range of 1 to 10 parts by weight.

[0020] Furthermore, a vinyl monomer may be added to the (meth)acrylate as necessary. Examples of the vinyl monomer include itaconic acid, maleic acid, crotonic acid, maleic anhydride, itaconic anhydride, vinyl acetate, N-vinylpyrrolidone, N-vinyl carboxylic acid amides, styrene, and N-vinyl caprolactam. These vinyl monomers may be used alone or in combination of two or more.

[0021] (Polymerization initiator) Examples of polymerization initiators that may be used optionally include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfide, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4,4-trimethylpentane), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-methyl-N-(phenylmethyl)-propionamidine]dihydrochloride, 2,2'-azobis[2-(3,4,5,6-tetrahydropyrimidin-2-yl)propane]dihydrochloride, and the like. Examples of the polymerization initiator include azo-based polymerization initiators such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]; persulfate-based polymerization initiators such as potassium persulfate and ammonium persulfate; peroxide-based polymerization initiators such as benzoyl peroxide, hydrogen peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, t-butyl peroxybenzoate, dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, 3,3,5-trimethylcyclohexanoyl peroxide and t-butyl peroxypivalate; and redox-based polymerization initiators composed of persulfates and sodium hydrogen sulfite. These polymerization initiators may be used alone or in combination of two or more. In addition, ultraviolet irradiation or radiation irradiation may be performed. The polymerization initiator is preferably used in the range of 0.005 to 1 part by weight per 100 parts by weight of the acrylic monomer. By using the polymerization initiator in this range, an acrylic polymer with excellent adhesive properties can be formed.

[0022] (Ionic Liquid) Ionic liquids are a combination of cations and anions that are liquid at room temperature, and are also called room temperature molten salts. Ionic liquids have properties such as non-flammability, non-volatility, and chemical stability. When a voltage is applied to an ionic liquid, anions migrate to the anode side and cations migrate to the cathode side. It is believed that the adhesion of the electrically peelable adhesive composition is weakened by the migration of anions and cations to the vicinity of the electrode, or by the occurrence of an oxidation-reduction reaction of anions or cations at the interface between the electrode and the electrically peelable adhesive composition, resulting in improved releasability.

[0023] The ionic conductivity of the ionic liquid is not particularly limited, but is preferably 10 -7 It is preferable that the ionic conductivity is 10 S / cm or more. -6 ~10 -1 It is preferable that the ionic conductivity is 10 -4 ~10 -2 More preferably, the ionic conductivity is 10 -3 ~10 -2 It is more preferable that the ionic liquid has an ionic conductivity of 100 S / cm. The ionic conductivity can be measured, for example, by an AC impedance method. The ionic conductivity of the ionic liquid can be measured, for example, by the following method by the AC impedance method.

[0024] At room temperature, an ionic liquid is placed on a stainless steel plate using a bipolar cell, and another stainless steel plate is placed on top of the ionic liquid to sandwich the ionic liquid between the stainless steel plates, and a spacer is used to control the shape of the ionic liquid into a disk of a certain area and thickness, thereby obtaining a sample. A voltage is applied to this sample, and the frequency that determines the amplitude is changed. The Cole-Cole plot obtained is then curve-fitted using an equivalent circuit to determine the bulk resistance (Ω). The ionic conductivity δ of the ionic liquid can be calculated by substituting the sample area A, sample thickness L, and bulk resistance Rb into the following formula. δ = L / (Rb × A) [δ: ionic conductivity, Rb: bulk resistivity, L: sample thickness (cm), A: sample area (cm 2 )]

[0025] The ionic liquid may, for example, be a combination of a cyclic cation and an anion represented by the following formula (1).

[0026] [ka] [In the formula, R 1 is a divalent hydrocarbon group having 2 to 8 carbon atoms which may contain a heteroatom, and N + Together with R 2 and R 3 are the same or different and are a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (however, when a nitrogen atom forms a double bond with an adjacent carbon atom, R 3 does not exist), X - is Cl - , Br - , I - , AlCl4 - , Al2Cl7-, NO3 - , BF4 - , PF6 - , ClO4 - , CH3COO - , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (FSO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6-, F(HF) n - , B(C6H5)4 - , C4F9SO3 - , CF3(CF2)3SO3 - , (CF3CF2SO2)2N - and CF3CF2COO - is an anion selected from

[0027] In the above formula, R 1 and N +The ring formed of includes rings in which at least one carbon atom constituting a hydrocarbon ring, such as saturated alicyclic hydrocarbons such as cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, and cyclooctane, and unsaturated cyclic hydrocarbons such as cyclopropene, cyclobutene, cyclopentene, cyclohexene, cycloheptene, cyclooctene, cyclopentadiene, and benzene, is replaced with a nitrogen atom. Examples of heteroatoms include N, O, S, and P, and N is preferred.

[0028] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group. The alkyl group having 3 to 8 carbon atoms includes structural isomers.

[0029] Other examples of ionic liquids include combinations of cations and anions represented by the following formula (2) or (3).

[0030] [ka] [wherein Y is N or P, and R 4 ~R 7 are the same or different and each represents a hydrogen atom (provided that R 4 ~R 7 are not all hydrogen atoms) or a linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, which may have a substituent (however, when a nitrogen atom forms a double bond with an adjacent carbon atom, R 7 is absent), the substituents are selected from the group consisting of halogen atoms, hydroxy groups, nitro groups, and cyano groups; X - is Cl - , Br - , I - , AlCl4 - , Al2Cl7-, NO3 - , BF4 - , PF6 - , ClO4 - , CH3COO - , CF3COO - , CF3SO3- , (CF3SO2)2N - , (FSO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6-, F(HF) n - , B(C6H5)4 - , C4F9SO3 - , CF3(CF2)3SO3 - , (CF3CF2SO2)2N - and CF3CF2COO - is an anion selected from

[0031] [ka] [In the formula, R 8 ~R 10 are the same or different and each represents a hydrogen atom (provided that R 8 ~R 10 are not all hydrogen atoms) or a linear, branched or cyclic alkyl group having 1 to 20 carbon atoms which may have a substituent, the substituent being selected from the group consisting of a halogen atom, a hydroxy group, a nitro group and a cyano group; X - is Cl - , Br - , I - , AlCl4 - , Al2Cl7-, NO3 - , BF4 - , PF6 - , ClO4 - , CH3COO - , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (FSO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6-, F(HF) n - , B(C6H5)4 - , C4F9SO3 - , CF3(CF2)3SO3- , (CF3CF2SO2)2N - and CF3CF2COO - is an anion selected from

[0032] The cation in the ionic liquid preferably has a weight average molecular weight of 700 or less, more preferably a weight average molecular weight of 50 to 600, more preferably a weight average molecular weight of 50 to 500, and more preferably a weight average molecular weight of 50 to 400. The upper limit of the weight average molecular weight of the cation in the ionic liquid is, for example, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250, 200, or 150. The lower limit of the weight average molecular weight of the cation in the ionic liquid is, for example, 30, 40, 50, 60, 70, 80, 90, 99, or 100. The weight average molecular weight here refers to the weight average molecular weight in terms of polystyrene.

[0033] The ionic liquid is preferably a combination of a cyclic cation represented by formula (1) and an anion, and is preferably a combination of a cation selected from a pyridinium-based cation, a cyclic aliphatic ammonium cation, and an imidazolium-based cation, and (FSO2)2N - , (CF3SO2)2N - and BF4 - From the viewpoint of improving the peelability after application of a voltage, a combination of a cation selected from the imidazolium-based cations and an anion selected from (FSO2)2N-, (CF3SO2)2N-, and BF4- is more preferable.

[0034] Ionic liquids are available from Daiichi Kogyo Seiyaku, Kanto Chemical, Koei Chemical Industry, and the like. For example, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMI-TFSI) can be obtained from Daiichi Kogyo Seiyaku, 1-hexylpyridinium bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide and 1-ethyl-3-methylimidazolium tetrafluoroborate can be obtained from Kanto Chemical, and 1-ethyl-3-methylimidazolium hexafluorophosphate (IL-C3), 1-butylpyridinium tetrafluoroborate (IL-P10) and 1-hexylpyridinium bis(trifluoromethanesulfonyl)imide (IL-P14) can be obtained from Koei Chemical Industry. The combination of cations and anions contained in EMI-FSI is as follows.

[0035] [ka]

[0036] The amount of ionic liquid contained in the electrically peelable pressure-sensitive adhesive composition is not particularly limited, but is preferably 1 to 90 parts by weight, more preferably 5 to 80 parts by weight, more preferably 5 to 50 parts by weight, more preferably 5 to 40 parts by weight, and more preferably 5 to 30 parts by weight, relative to 100 parts by weight of the acrylic polymer. The upper limit of the amount of ionic liquid contained in the electrically peelable pressure-sensitive adhesive composition is, for example, 90 parts by weight, 85 parts by weight, 80 parts by weight, 70 parts by weight, 60 parts by weight, 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 33 parts by weight, 32 parts by weight, 31 parts by weight, or 30 parts by weight, relative to 100 parts by weight of the acrylic polymer. The lower limit of the amount of ionic liquid contained in the electrically peelable pressure-sensitive adhesive composition is, for example, 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 9 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, or 20 parts by weight relative to 100 parts by weight of the acrylic polymer. The ionic liquid may be a combination of one cation and one anion, or a combination of multiple types of cations and anions.

[0037] (Super absorbent polymer) The electrically peelable pressure-sensitive adhesive composition of the present embodiment contains a highly water-absorbent polymer. In this specification, a highly water-absorbent polymer refers to a polymer that can absorb at least 10 times its own weight in water. It is preferable that the highly absorbent polymer is capable of absorbing 20 times or more its own weight in water, more preferably 30 times or more its own weight in water, more preferably 50 times or more its own weight in water, and even more preferably 100 times or more its own weight in water. The term "weight" as used herein refers to the dry weight of the highly water-absorbent polymer. It is believed that the incorporation of the highly water-absorbent polymer allows the electrically peelable pressure-sensitive adhesive composition to retain water, thereby improving the deterioration of the electrically peelable property due to high temperatures, but the present invention is not limited to any particular theory.

[0038] Examples of the highly water-absorbent polymer include sodium poly(meth)acrylate, potassium poly(meth)acrylate, ammonium poly(meth)acrylate, calcium poly(meth)acrylate, magnesium poly(meth)acrylate, hydroxyethyl cellulose, hydroxypropyl cellulose, poly(meth)acrylamide, poly-N-isopropylamide, polyvinylpyrrolidone, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, and derivatives and crosslinked products thereof. Derivatives are not particularly limited, but examples include those in which the side chains of the above polymers are substituted with a hydroxyl group, a carboxyl group, an amide group, an alkyl group (e.g., having 1 to 6 carbon atoms), an aryl group (e.g., having 6 to 8 carbon atoms), or a halogen. Among these, those substituted with a hydrophilic group (e.g., a hydroxyl group, a carboxyl group, an amide group, etc.) are preferred. The highly water-absorbent polymer is preferably sodium poly(meth)acrylate, potassium poly(meth)acrylate, ammonium poly(meth)acrylate, calcium poly(meth)acrylate, magnesium poly(meth)acrylate, or a derivative or crosslinked product thereof, more preferably sodium polyacrylate or a derivative or crosslinked product of sodium polyacrylate. These highly water-absorbent polymers may be used alone or in combination.

[0039] The amount of the highly absorbent polymer contained in the electrically peelable pressure-sensitive adhesive composition is not particularly limited, but is preferably 1 to 90 parts by weight, more preferably 1 to 80 parts by weight, more preferably 1 to 70 parts by weight, more preferably 1 to 60 parts by weight, more preferably 1 to 50 parts by weight, and more preferably 1 to 40 parts by weight, relative to 100 parts by weight of the acrylic polymer. The upper limit of the amount of the highly absorbent polymer contained in the electrically peelable pressure-sensitive adhesive composition is, for example, 90 parts by weight, 85 parts by weight, 80 parts by weight, 70 parts by weight, 60 parts by weight, 50 parts by weight, 40 parts by weight, 35 parts by weight, or 30 parts by weight, relative to 100 parts by weight of the acrylic polymer. The lower limit of the amount of the highly absorbent polymer contained in the electrically peelable pressure-sensitive adhesive composition is, for example, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, or 5 parts by weight, relative to 100 parts by weight of the acrylic polymer.

[0040] By using a highly water-absorbent polymer, the electrically peelable adhesive composition is one whose electrical peelability is not easily reduced even when exposed to high temperatures. The term "high temperature" refers to a temperature of 40° C. or higher. In this embodiment, "the electrically peelable adhesive composition is exposed to high temperatures" means that the electrically peelable adhesive composition is present in an environment in which the composition itself can become hot. Examples of such environments include a state in which the electrically peelable adhesive composition is in direct or indirect contact with a high-temperature object, a state in which the electrically peelable adhesive composition is placed in a high-temperature space, and both. The environment in which the electrically peelable adhesive composition itself can become hot may be a constantly high-temperature environment or an environment that becomes hot for a predetermined period of time. Since the electrically peelable adhesive composition of the present invention has excellent electrical peelability even when exposed to high temperatures, it can be used even when the object to which it is attached can become hot itself or when the space in which the electrically peelable adhesive composition is placed becomes hot.

[0041] Here, whether the electrically peelable adhesive composition has excellent electrical peeling properties even when exposed to high temperatures can be judged by a decrease in pull-up strength of 85% or more after the electrically peelable adhesive composition is left standing in a space at 40°C for 500 hours, as calculated by the following formula (4) or (5). Alternatively, whether the electrically peelable adhesive composition has excellent electrical peeling properties even when exposed to high temperatures can be judged by a decrease in pull-up strength of 20% or more after the electrically peelable adhesive composition is left standing in a space at 80°C for 100 hours, as calculated by the following formula (6) or (7). The decrease in pull-up strength of the electrically peelable adhesive composition after being left standing in a space at 40°C for 500 hours, as calculated by the formula (4) or (5), is preferably 90% or more. The decrease in pull-up strength of the electrically peelable adhesive composition after being left standing in a space at 80°C for 100 hours, as calculated by the formula (6) or (7), is preferably 30% or more. It is more preferable that the rate of decrease in pull-up strength after the electrically peelable pressure-sensitive adhesive composition is allowed to stand in a space at 40°C for 500 hours, as calculated by formula (4) or (5), is 90% or more, and that the rate of decrease in pull-up strength after the electrically peelable pressure-sensitive adhesive composition is allowed to stand in a space at 80°C for 100 hours, as calculated by formula (6) or (7), is 30% or more.

[0042]

number

[0043]

number

[0044]

number

[0045]

number

[0046] In formula (4) or (6), peeling refers to a state where the adherend and the object to be fixed are not in contact with each other. In formula (5) or (7), peeling refers to a state where the resin plate and the stainless steel plate are not in contact with each other. For example, using a tensile tester, completely disengaging the adherend and the object to be fixed may be achieved by pulling the object to be fixed using a tensile tester, by pulling an adhesive product, or by pulling a conductive auxiliary attached to the adherend or the object to be fixed. The adherend or the object to be fixed may or may not be conductive (fixing, adherend, object to be fixed, and conductive auxiliary in the formula will be described later). An example of a tensile tester is the Autograph (registered trademark) AGS-H manufactured by Shimadzu Corporation.

[0047] Conventional electrically releasing adhesive compositions lose their electrical peeling properties when exposed to high temperatures, and the adhesive strength does not decrease to a level sufficient for peeling even when a voltage is applied. The electrically releasing adhesive composition of the present invention can reduce its adhesive strength to a level sufficient for peeling by applying a voltage even when exposed to high temperatures, and is therefore suitable for use under conditions of exposure to high temperatures.

[0048] (Mobility promoter) In this embodiment, the electrically peelable pressure-sensitive adhesive composition may contain a migration promoter that aids in the migration of ions when a voltage is applied. Examples of the migration promoter include polyethylene glycol and alkyl ethers of polyethylene glycol, and alkyl ethers of polyethylene glycol are preferred.

[0049] The molecular weight of the migration promoter is not particularly limited, but it is preferable that the migration promoter has a weight average molecular weight of 120 to 600, more preferably a weight average molecular weight of 120 to 550, more preferably a weight average molecular weight of 120 to 500, and more preferably a weight average molecular weight of 120 to 360. The upper limit of the weight average molecular weight of the migration promoter is, for example, 600, 590, 580, 570, 560, 550, 540, 530, 520, 510, 500, 490, 480, 470, 460, 450, 440, 430, 420, 410, 400, 390, 380, 370, 360, 355, 350, or 340. The lower limit of the weight average molecular weight of the migration promoter is, for example, 120, 125, 130, 135, 140, 145, 150, 155, 160, or 170. The weight average molecular weight referred to here refers to the weight average molecular weight calculated in terms of polystyrene.

[0050] Examples of the alkyl ether of polyethylene glycol include polyethylene glycol mono(di)methyl ether, polyethylene glycol mono(di)ethyl ether, polyethylene glycol mono(di)propyl ether, polyethylene glycol mono(di)isopropyl ether, polyethylene glycol mono(di)butyl ether, polyethylene glycol mono(di)isobutyl ether, polyethylene glycol mono(di)methyl ether, and polyethylene glycol mono(di)pentyl ether. Among these, an alkyl ether of polyethylene glycol having a weight average molecular weight of 120 to 360 is preferred, and a polyethylene glycol mono(di)methyl ether having a weight average molecular weight of 120 to 360 is more preferred, and is more preferably selected from tetraethylene glycol dimethyl ether (dimethyl tetraglycol), diethylene glycol dibutyl ether, triethylene glycol butyl methyl ether, dimethyl triglycol, and triethylene glycol monomethyl ether, and more preferably tetraethylene glycol dimethyl ether. The alkyl ether of polyethylene glycol is available from Nippon Nyukazai Co., Ltd., Toho Chemical Industry Co., Ltd., and the like. The alkyl ether of polyethylene glycol used may be used alone or in combination of two or more kinds.

[0051] The amount of the migration promoter contained in the electrically peelable pressure-sensitive adhesive composition is not particularly limited, and may be, for example, 1 to 90 parts by weight, 5 to 80 parts by weight, 5 to 50 parts by weight, 5 to 40 parts by weight, or 5 to 30 parts by weight, relative to 100 parts by weight of the acrylic polymer. The upper limit of the migration promoter contained in the electrically peelable pressure-sensitive adhesive composition is, for example, 90 parts by weight, 80 parts by weight, 70 parts by weight, 60 parts by weight, 50 parts by weight, 40 parts by weight, or 30 parts by weight, relative to 100 parts by weight of the acrylic polymer. The lower limit of the migration promoter contained in the electrically peelable pressure-sensitive adhesive composition is, for example, 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 9 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, or 20 parts by weight, relative to 100 parts by weight of the acrylic polymer.

[0052] (Organic solvent) In order to easily apply the electrically peelable adhesive composition to a substrate, a release film or a release paper, the electrically peelable adhesive composition may contain an organic solvent. The organic solvent is not particularly limited, and includes known organic solvents that can be used for adhesives. As the organic solvent, either a hydrophilic organic solvent or a hydrophobic organic solvent may be used. Examples of hydrophilic organic solvents include methanol, ethanol, 1-propanol, 2-propanol, n-butyl alcohol, sec-butyl alcohol, isobutanol, tert-butyl alcohol, acetonitrile, acetone, dimethylformamide, and the like. Examples of hydrophobic organic solvents include aliphatic hydrocarbons such as hexane, heptane, and isooctane, esters such as methyl acetate, ethyl acetate, and propyl acetate, aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene, halogenated hydrocarbons such as dichloromethane, 1,2-dichloroethane, chloroform, 1-chlorobutane, and chlorobenzene, ethers such as diethyl ether and t-butyl methyl ether, and ketones such as methyl ethyl ketone and methyl isobutyl ketone. These organic solvents may be used alone or in combination of two or more. When using an organic solvent, it is preferable to adjust the usage ratio so that the solid content of the acrylic polymer is 10% by weight or more. It is more preferable that the usage ratio is adjusted so that the solid content is 20 to 50% by weight.

[0053] (Additives) The electrically peelable adhesive composition of the present embodiment may contain additives such as a conductive material, a filler, a plasticizer, an antioxidant, a flame retardant, a colorant, a surfactant, or an adhesive other than the above acrylic polymer.

[0054] Conductive materials are mainly classified into carbon-based conductive materials and metal-based conductive materials. Carbon-based conductive materials include, for example, nanocarbon or carbon fiber [e.g., vapor grown carbon fiber (VGCF) or carbon nanofiber], more specifically, natural graphite, artificial graphite, acetylene black, ketjen black, furnace black, etc. Metal-based conductive materials include, for example, metals such as Cu, Ni, Al, Ag, Au, Pt, Zn, or Mn, or alloys thereof. The conductive materials may be used alone or in combination.

[0055] Examples of the filler include silica, diatomaceous earth, alumina, zinc oxide, magnesium oxide, calcium carbonate, magnesium carbonate, calcium sulfate, barium sulfate, calcium silicate, talc, mica, bentonite, activated clay, glass fiber, aluminum nitride, etc. The fillers may be used alone or in combination of two or more kinds.

[0056] Examples of the plasticizer include polyols such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol, aliphatic polycarboxylates such as adipates, citric acids, sebacates, azelates, and maleates, aromatic polycarboxylates such as terephthalates, isophthalates, phthalates, trimellitates, and benzoates, polyesters, etc. The plasticizers may be used alone or in combination.

[0057] Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, lactone-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, etc. The antioxidants may be used alone or in combination of two or more kinds.

[0058] Examples of the flame retardant include phosphorus- and halogen-containing organic compounds, bromine- or chlorine-containing organic compounds, ammonium polyphosphate, aluminum hydroxide, antimony oxide, and reactive flame retardants. The flame retardants may be used alone or in combination.

[0059] Examples of the colorant include inorganic pigments such as carbon black, titanium oxide, zinc oxide, iron oxide, and mica, and organic pigments such as coupling azo pigments, condensed azo pigments, anthraquinone pigments, thioindigo pigments, dioxazone pigments, and phthalocyanine pigments. The colorant may be used alone or in combination.

[0060] Examples of the surfactant include anionic surfactants such as alkylbenzenesulfonate, α-olefinsulfonate, and phosphoric acid ester, cationic surfactants such as amine salts (alkylamine salts, imidazolines, etc.), and quaternary ammonium salts (dialkyldimethylammonium salts, alkylbenzyldimethylammonium salts, pyridinium salts, and benzethonium chloride, etc.), and nonionic surfactants such as sorbitan tristearate, sorbitan monopalmitate, sorbitan trioleate, stearic acid monoglyceride, polyoxyethylene nonylphenyl ether, and polyoxyethylene dodecyl ether. The surfactants may be used alone or in combination.

[0061] Examples of adhesives other than the acrylic polymer include silicone adhesives, polyester adhesives, urethane adhesives, and rubber adhesives. Examples of silicone adhesives include dimethylsiloxane and diphenylsiloxane adhesives. Examples of polyester adhesives include polyesters obtained by polycondensation of a carboxylic acid component having two or more functional groups and a diol component. Examples of urethane adhesives include urethane polymers obtained by reacting a polyol with a polyisocyanate compound. Examples of rubber adhesives include synthetic rubbers such as styrene-isoprene block copolymers, styrene-butadiene-styrene block copolymers, styrene-butadiene rubber, polyisoprene rubber, polyisobutylene, and butyl rubber, and natural rubbers.

[0062] The amount of these adhesives other than the acrylic polymers is 40 parts by weight or less, preferably 35 parts by weight or less, more preferably 30 parts by weight or less, more preferably 20 parts by weight or less, more preferably 10 parts by weight or less, more preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and more preferably no adhesives other than the acrylic polymer are included, relative to 100 parts by weight of the acrylic polymer.

[0063] The amount of these additives (excluding adhesives other than the above-mentioned acrylic polymer) contained in the electrically peelable adhesive composition is not particularly limited, but can be, for example, in the range of 0.1 to 200 parts by weight, or in the range of 1 to 100 parts by weight, per 100 parts by weight of the acrylic polymer.

[0064] (Method of producing electrically releasing adhesive composition) The electrically peelable adhesive composition of the present embodiment can be produced by stirring an acrylic polymer, an ionic liquid, a highly absorbent polymer, and optionally a migration promoter, a crosslinking agent, and the like. The stirring method is not particularly limited, and a known stirring method can be used. Specifically, for example, an acrylic polymer, an ionic liquid, a highly absorbent polymer, and optionally a migration promoter, a crosslinking agent, and the like can be stirred with a V-type mixer or mixer (dissolver, homomixer, planetary mixer, etc.). The above-mentioned additives may be added during stirring.

[0065] (Uses of the Electrically Peelable Adhesive Composition) The electrically peelable adhesive composition of the present embodiment has excellent electrical peelability even when exposed to high temperature conditions. Therefore, the electrically peelable adhesive composition is suitable for use under conditions where the conventional electrically peelable adhesive composition could not be used because of the deterioration of electrical peelability. Examples of such conditions include the surroundings of the engine of a car, the surroundings of the drive unit of a home appliance, and during the manufacture of electronic parts and metal parts.

[0066] As described above, the electrically peelable adhesive composition of the present embodiment is suitable for use under conditions where the temperature may be high, but this does not deny the use under conditions where the temperature is only room temperature, and even under such conditions, it can be suitably used in the same way as conventional electrically peelable adhesive compositions. That is, the electrically peelable adhesive composition of the present embodiment can be easily peeled off from a conductive object by applying a voltage without performing UV irradiation or heat treatment, so that the electrically peelable adhesive composition can be suitably used for adhesive fixation of non-transparent members that cannot be irradiated with UV or members that are weak against heat. For example, when products such as home appliances and PCs contain highly valuable parts or parts that are to be safely collected and reused, the parts can be fixed with the electrically peelable adhesive composition of the present invention and sold, and then the used home appliances, personal computers, etc. are collected, and the fixed parts can be easily re-collected by applying a voltage to them. The fact that parts, etc. can be easily re-collected is also useful from the viewpoint of recycling and reuse. Alternatively, it can be suitably used for fixing members that require high processing accuracy or for fixing members that are difficult to physically fix, such as thin metal plates and substrates. For example, the electrically peelable adhesive composition can be used for temporarily fixing components in the electronic component manufacturing process (for example, temporarily fixing wafers during dicing of LSI chips), and the temporarily fixed components can be easily released by applying a voltage. Other applications include bonding sensors to conductive objects. In this application, the sensor can be easily recovered by peeling it off by applying a low voltage, and the sensor can be used repeatedly, which is economical.

[0067] The adhesiveness of the electrically peelable adhesive composition of the present embodiment is restored over time after voltage application. Therefore, the electrically peelable adhesive composition after voltage application can be reused. This is because the anions and cations in the ionic liquid that have moved in opposite directions due to voltage application move again to become uniform in the electrically peelable adhesive composition over time. Therefore, the electrically peelable adhesive composition of the present embodiment can be used repeatedly as an adhesive, making it economical and useful from the viewpoints of recycling and reuse.

[0068] (Electrically peelable adhesive products) The electrically peelable adhesive product of this embodiment (hereinafter also simply referred to as the adhesive product) is composed of a substrate and an electrically peelable adhesive layer formed so as to be in contact with the substrate. In another embodiment of the adhesive product, the product is composed of a core material and two electrically peelable adhesive layers formed so as to be in contact with both sides of the core material.

[0069] The electrically peelable adhesive layer of the adhesive product contains an electrically peelable adhesive composition. The adhesive product of the present embodiment functions as a substance that fixes a substance (referred to as a fixing target) that is to be fixed to an adherend by the adhesive product to the adherend.

[0070] The shape of the pressure-sensitive adhesive product is not particularly limited, and may be an appropriate shape depending on the application, such as, for example, a pressure-sensitive adhesive tape, a pressure-sensitive adhesive sheet, etc. The surface of the electrically peelable pressure-sensitive adhesive layer to be used may be protected by a release-treated polyethylene terephthalate film or release paper until use.

[0071] The adherend of the present embodiment refers to an object that provides a place to which an object to be fixed is fixed via the electrically releasing adhesive composition, electrically releasing adhesive layer, or adhesive product of the present embodiment. Here, fixing can be direct or indirect, with direct fixing referring to a state in which the adherend and the object to be fixed are in direct contact with the adhesive product, and indirect fixing referring to a state in which the adherend and / or the object to be fixed are not in direct contact with the adhesive product but are in contact with the adhesive product via a conductive auxiliary material. As long as the object to be fixed can be fixed to the adherend, the fixing method can be either direct or indirect.

[0072] The adherend may be either a conductive adherend (conductive adherend) or a non-conductive adherend (non-conductive adherend). When the adherend is a conductive adherend, the adhesive product may be directly attached to the adherend. When the adherend is a non-conductive adherend, it is essential to attach a conductive auxiliary material to the non-conductive adherend. When attaching the conductive auxiliary material, any adhesive such as a commercially available adhesive is used.

[0073] Examples of conductive adherends include metal plates, metal products, metal work tables, etc., made of metals such as iron, aluminum, copper, silver, gold, etc., or alloys of these metals. Examples of non-conductive adherends include wooden plywood, plastic products, non-metal work tables, etc.

[0074] The object to be fixed in this embodiment is not particularly limited, but if the object to be fixed has conductivity, the object to be fixed may be directly attached to the adhesive product. If the object to be fixed is non-conductive, it is essential to attach a conductive auxiliary material to the object to be fixed and then attach it to the adhesive product, as in the case of a non-conductive adherend.

[0075] Examples of conductive objects to be fixed include metals such as iron, aluminum, copper, silver, and gold, or alloys of these metals, foils (thickness less than 100 μm), plates (thickness 100 μm or more), meshes or cloths containing fibers mixed with or coated with these metals or alloys, resin sheets containing these metals or alloys, resin plates provided with a layer containing these metals, alloys, or conductive metal oxides, etc. Examples of non-conductive objects to be fixed include resin, wood, and plastic plates, etc.

[0076] The substrate in the present embodiment refers to a planar object to which the electrically releasing pressure sensitive adhesive composition is applied. The substrate may be conductive or non-conductive. Examples of substrates used in adhesive products include foils or plates made of metals such as aluminum, copper, silver, and gold, or alloys of these metals, films of polyethylene terephthalate (PET) and polyimide, carbon fibers, paper, woven fabrics, and nonwoven fabrics, and the thickness is not particularly limited. However, nonconductive substrates used in adhesive products are peeled off before use. These can be selected appropriately depending on the shape of the electrically peelable adhesive product to be used. The substrate or core material may be one in which the applied electrically peelable adhesive composition adheres directly to the surface of the substrate or core material, or one in which the applied electrically peelable adhesive composition permeates into the gaps between the fibers of the substrate or core material. Examples of such substrates include paper and nonwoven fabric.

[0077] The electrically peelable adhesive layer may be formed on one side of the substrate, or on both sides. In this case, the substrate is called a core material. It is essential that the core material is capable of passing ionic liquid between the electrically peelable adhesive layers on both sides when a voltage is applied. When the core material is a material capable of passing ionic liquid, the adhesive strength can be reduced by applying a voltage to the electrically peelable adhesive layers on both sides. By using a substrate or core material, the adhesive product can be made stronger, and the workability during use can be improved.

[0078] The conductive auxiliary material is not particularly limited as long as it is conductive, and examples thereof include metals such as aluminum, copper, silver, gold, etc., alloys of these metals, or films on which conductive metal oxides (such as indium tin oxide: ITO) are vapor-deposited; cloth containing fibers mixed with or coated with these metals or alloys; resin sheets containing these metals or alloys; and resin plates having a layer containing these metals, alloys, or conductive metal oxides.

[0079] FIG. 1 shows an example of a cross section of an adhesive product in the form of a single-sided tape (a cross section when a tape attached to a horizontal surface is cut vertically; the same applies below), and FIG. 2 shows an example of a cross section of an adhesive product in the form of a double-sided tape. FIGS. 3A to 7B show circuit examples when a voltage is applied to the electrically peelable adhesive layer of these adhesive products via a conductive object, and peeling examples after the voltage application. The use form of the adhesive product of the present invention is not limited to the following circuit examples and peeling examples. In the following peeling examples, the electrically peelable adhesive layer or the adhesive product is described as remaining on the adherend side, but peeling can be performed so that the adhesive product remains on the object to be fixed by reversing the positive and negative directions of the DC power sources in each example. In addition, which side of the power source the adhesive product remains on depends on the composition of the adhesive product, and is not particularly limited.

[0080] In the figure, 1 denotes an electrically peelable adhesive layer, 2 denotes a substrate or core material, 3 denotes a conductive adherend, 4 denotes a DC power source, 5 denotes a conductive object to be fixed, 6 denotes a non-conductive object to be fixed, 7 denotes any pressure-sensitive adhesive, 8 denotes a conductive auxiliary material, and 9 denotes a non-conductive adherend.

[0081] Fig. 3A shows an example of a cross section of an adhesive product in the form of a single-sided tape adhered to a conductive adherend 3 and voltage applied thereto. The substrate 2 here is a material having electrical conductivity. As shown in Fig. 3A, terminals are connected to the substrate 2 and the conductive adherend 3, and a circuit is formed with a DC power source 4, thereby applying a voltage to the electrically peelable adhesive layer 1, and the adhered conductive substrate 2 can be peeled off from the conductive adherend 3 as shown in Fig. 3B.

[0082] Fig. 4A shows an example of a cross section in which a conductive object to be fixed 5 is adhered to a conductive adherend 3 using an adhesive product in the form of a double-sided tape and a voltage is applied. The double-sided tape has an electrically peelable adhesive layer 1 formed on both sides of a core material 2. As shown in Fig. 4A, terminals are connected to the conductive object to be fixed 5 and the conductive adherend 3, and a circuit is formed with a DC power source 4, thereby applying a voltage to the electrically peelable adhesive layer 1, and the adhered conductive object to be fixed 5 can be peeled off from the conductive adherend 3 as shown in Fig. 4B.

[0083] FIG. 5A shows an example of a cross section in which a non-conductive object 6 is attached to a conductive adherend 3 using an adhesive product in the form of a double-sided tape and a voltage is applied. As shown in FIG. 5A, an aluminum plate is attached to the non-conductive object 6 as a conductive auxiliary material 8 using any adhesive 7, and the non-conductive object 6, the conductive auxiliary material 8, and the conductive adherend 3 are attached using an adhesive product. By connecting terminals to the conductive auxiliary material 8 and the conductive adherend 3 and forming a circuit with a DC power source 4, a voltage is applied to the electrically peelable adhesive layer 1, and the non-conductive object 6 that has been attached can be peeled off from the conductive adherend 3 as shown in FIG. 5B. In this case, the conductive auxiliary material 8 attached to the non-conductive object 6 remains on the non-conductive object 6.

[0084] FIG. 6A shows an example of a cross section in which a conductive object 5 is attached to a non-conductive adherend 9 using an adhesive product in the form of a double-sided tape and a voltage is applied. As shown in FIG. 6A, an aluminum plate is attached to the non-conductive adherend 9 as a conductive auxiliary material 8 using any adhesive 7, and the conductive object 5, the conductive auxiliary material 8, and the non-conductive adherend 9 are adhered to each other using an adhesive product. By connecting terminals to the conductive object 5 and the conductive auxiliary material 8 and forming a circuit with a DC power source 4, a voltage is applied to the electrically peelable adhesive layer 1, and the adhered conductive object 5 can be peeled off from the non-conductive adherend 9 as shown in FIG. 6B.

[0085] FIG. 7A shows an example of a cross section in which a non-conductive object 6 is adhered to a non-conductive adherend 9 using an adhesive product in the form of a double-sided tape and a voltage is applied. As shown in FIG. 7A, an aluminum plate is attached as a conductive auxiliary material 8 to each of the non-conductive object 6 and the non-conductive adherend 9 using an arbitrary adhesive 7, and the conductive auxiliary material 8 to which the non-conductive object 6 is adhered and the conductive auxiliary material 8 to which the non-conductive adherend 9 is adhered are adhered using an adhesive product. By connecting terminals to each conductive auxiliary material 8 and forming a circuit with a DC power source 4, a voltage is applied to the electrically peelable adhesive layer 1, and the adhered non-conductive object 6 can be peeled off from the non-conductive adherend 9 as shown in FIG. 7B. In this case, the conductive auxiliary material 8 attached to the non-conductive object 6 remains on the non-conductive object 6.

[0086] The adhesive product of this embodiment can perform each of the above-mentioned peeling operations even by applying a low voltage of 30 V or less.

[0087] The electrically peelable adhesive layer can be formed, for example, by applying the electrically peelable adhesive composition to a substrate or core material. The method of applying the electrically peelable adhesive composition is not particularly limited, but for example, a spin coater, a gravure coater, an applicator, a multi-coater, a die coater, a bar coater, a roll coater, a blade coater, or a knife coater can be used. The thickness of the electrically peelable adhesive layer is not particularly limited, but is preferably in the range of 1 μm to 200 μm, more preferably in the range of 1 μm to 100 μm, and more preferably in the range of 1 μm to 50 μm. After applying the electrically peelable adhesive composition, the electrically peelable adhesive layer may be heated to dry the electrically peelable adhesive composition.

[0088] In the adhesive product of the present embodiment, the adhesiveness of the electrically peelable adhesive composition is restored over time after the voltage application. Therefore, the adhesive product after the voltage application is reusable. Since the adhesive product of the present embodiment can be used repeatedly, it is economical and useful from the viewpoint of recycling and reuse.

[0089] (Method of manufacturing electrically peelable adhesive products) One embodiment of the present invention is a method for producing an electrically releasing adhesive product. The electrically releasing adhesive product can be produced, for example, by applying an electrically releasing adhesive composition to a substrate or a core material to form an electrically releasing adhesive layer. The electrically releasing adhesive composition, the electrically releasing adhesive layer, the substrate, the electrically releasing adhesive product, and the application method are as described above.

[0090] When the electrically peelable adhesive product is in the form of an adhesive tape or an adhesive sheet, the thickness of the adhesive product is not particularly limited, but is preferably in the range of 1 to 200 μm, and more preferably in the range of 1 to 100 μm. The thickness of the electrically peelable adhesive layer or the adhesive product refers to a value measured using a known thickness measuring device, such as a Peacock precision measuring device.

[0091] (Removal method) The electrically peelable adhesive layer and adhesive product of this embodiment can be peeled off from the conductive object to which it is directly attached by applying a voltage after the electrically peelable adhesive layer or adhesive product is attached onto the conductive object.

[0092] As for the peeling method, for example, if the object to be fixed and the adherend are conductive, terminals can be connected to the object to be fixed and the adherend and a voltage can be applied between the terminals to peel off the electrically peelable adhesive layer or the adhesive product from the object to be fixed or the adherend. If the object to be fixed and / or the adherend are not conductive, the fixing and peeling operations can be performed even with non-conductivity by adhesively adhering an aluminum plate or the like as a conductive auxiliary material. These fixing and peeling operations are shown in the peeling examples of the adhesive product above.

[0093] The voltage to be applied is not particularly limited as long as it can peel off the electrically peelable adhesive layer or the adhesive product, but a low voltage is preferable in consideration of the size of the voltage application device, the effect on the object to be fixed, and the risk to the human body due to accidents during work. The range of the applied voltage is, for example, 690V, 650V, 600V, 550V, 500V, 480V, 450V, 415V, 400V, 380V, 350V, 347V, 300V, 250V, 240V, 230V, 220V, 210V, 208V, 200V, 180V, 160V, 150V, 130V, 125V, 120V, 115V, 110V, 105V, 100V, 90V, 80V, 70V, 60V, 50V, 40V, and 30V with the upper limit set to 0.5V, 1V, 2V, 3V, The lower limit of the voltage can be selected from the voltages of 4 V, 5 V, 6 V, 7 V, 8 V, 9 V, and 10 V. Among these, it is particularly preferable to operate at a voltage in the range of 1 to 30 V, because a compact application device is sufficient, and in terms of safety and the effect on the object to be fixed.

[0094] The electrically peelable adhesive layer and adhesive product of this embodiment can be peeled off from a conductive object even when a low voltage of about several V is applied, so that the peeling operation can be performed even when the power source is, for example, a commercially available dry cell. This shows that this embodiment is safe for workers and allows the peeling operation to be performed using a simple, portable voltage application device.

[0095] The voltage application time is not particularly limited as long as it can peel off the electrically peelable adhesive layer or the adhesive product, but taking into consideration the effect on the object to be fixed, it is preferably within 10 minutes, more preferably within 5 minutes, and even more preferably within 3 minutes.

[0096] The temperature during peeling is not particularly limited, but it is preferable to perform peeling at room temperature. Since the electrically peelable adhesive layer or adhesive product of the present embodiment can be peeled off from a conductive object at a low voltage and in a short time as described above, the effect of heat on the object to be fixed can be extremely reduced.

[0097] One embodiment of the present invention includes the use of an acrylic polymer, an ionic liquid, and a superabsorbent polymer for the preparation of an electrically peelable adhesive composition. The electrically peelable adhesive composition can be prepared by mixing the acrylic polymer, the ionic liquid, and the superabsorbent polymer so as to contain the acrylic polymer, optionally adding a crosslinking agent, additives, etc., and stirring by a known method. The superabsorbent polymer and the electrically peelable adhesive composition are as described above.

[0098] One embodiment of the present invention includes the use of an electrically releasing adhesive composition for the manufacture of an electrically releasing adhesive product. An electrically releasing adhesive product can be manufactured by forming an electrically releasing adhesive layer on a substrate (or core material) using the electrically releasing adhesive composition. The electrically releasing adhesive composition, the electrically releasing adhesive layer, the substrate, and the electrically releasing adhesive product are as described above. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these in any way.

[0100] Example 1 An adhesive product was prepared using an acrylic polymer, an ionic liquid, a transport promoter, and a highly water-absorbent polymer as follows. 1. Preparation of acrylic polymer A monomer mixture consisting of 91 parts by weight of n-butyl acrylate (Mitsubishi Chemical), 8 parts by weight of acrylic acid (Mitsubishi Chemical), and 1 part by weight of 2-hydroxyethyl methacrylate (Nippon Shokubai) and 186 parts by weight of polymerization solvent (ethyl acetate:toluene (weight ratio) = 9:1) were placed in a glass flask and replaced with nitrogen gas. 0.2 parts by weight of azobisisobutyronitrile (AIBN, Junsei Chemical) was added as a polymerization initiator, and the temperature was raised to 85°C and polymerization reaction was carried out for 5 hours to obtain an acrylic adhesive. The obtained acrylic adhesive contained 35% by weight of acrylic polymer (weight average molecular weight approximately 800,000, Tg-46°C) and had a viscosity of 7,000 mPa·s.

[0101] 2. Preparation of Electrically Releasable Adhesive Composition 100 parts by weight of the acrylic adhesive (35 parts by weight of acrylic polymer) was mixed with 5.0 parts by weight of Coronate L-55E (Tosoh Corporation) as an isocyanate crosslinking agent and 7.0 parts by weight of dimethyltetraglycol (Nippon Nyukazai Co., Ltd.: molecular weight about 220) as a migration promoter, and stirred with a dissolver at room temperature for 10 minutes. After stirring, 7.0 parts by weight of Elexcel (registered trademark) AS-110 (EMI-FSI: Daiichi Kogyo Seiyaku Co., Ltd.) was further added as an ionic liquid and stirred with a dissolver at room temperature for 10 minutes. After the second stirring, 1.75 parts by weight of Aqualic CS 6S (registered trademark: Nippon Shokubai Co., Ltd.) was added as a highly water-absorbent polymer, and similarly stirred with a dissolver for 10 minutes at room temperature and left to defoam, to obtain an electrically peelable adhesive composition.

[0102] 3. Preparation of adhesive products The electrically peelable adhesive composition obtained in 2 was applied to a polyethylene terephthalate film whose surface had been treated with silicone, and dried at 100°C for 5 minutes. The surface of the dried film coated with the electrically peelable adhesive composition was attached to a nonwoven fabric [Milife (registered trademark) TY0503FE (ENEOS Techno Materials)]. Similarly, a film was prepared by applying and drying the electrically peelable adhesive composition to a polyethylene terephthalate film whose surface had been treated with silicone, and the film was attached to the surface of the nonwoven fabric to which the film was not attached. The film was then left to stand at 40°C for 3 days to obtain the adhesive product of Example 1 (double-sided tape, thickness 80 μm).

[0103] Comparative Example 1 An adhesive product of Comparative Example 1 was obtained in the same manner as in Example 1, except that no highly water-absorbent polymer was used.

[0104] Example 2 An adhesive product of Example 2 was obtained in the same manner as in Example 1, except that the amount of the highly water-absorbent polymer was 3.5 parts by weight per 100 parts by weight of the acrylic adhesive.

[0105] Example 3 An adhesive product of Example 3 was obtained in the same manner as in Example 1, except that the amount of the highly water-absorbent polymer was 7.0 parts by weight per 100 parts by weight of the acrylic adhesive.

[0106] Example 4 An adhesive product of Example 4 was obtained in the same manner as in Example 1, except that the highly water-absorbent polymer was Sunfresh (registered trademark) ST-500MPSA (Sanyo Chemical Industries, Ltd.).

[0107] Preparation of evaluation samples A commercially available double-sided tape (RD-7020 manufactured by Big Technos) without electrical peeling property was attached to one side of an ABS resin plate (fixing object) with a thickness of 3 mm, a length of 50 mm, and a width of 30 mm. A 50 μm thick aluminum foil (conductive auxiliary material) was attached to the side of the double-sided tape where the ABS resin was not attached. After attaching the aluminum foil, the release film on one side of each adhesive product of Examples 1 to 4 and Comparative Example 1 cut to a length of 50 mm x 30 mm was peeled off and attached to the other side of the aluminum foil where both the ABS resin of the aluminum foil and the commercially available double-sided tape were attached. The release film on the other side of the adhesive product was peeled off and the product was attached to a polished stainless steel plate (conductive adherend: 125 mm x 50 mm). A 2 kg rubber roller was used to make one reciprocating movement in the long side direction of the adhesive product at a speed of 300 mm / min to press the adherend, adhesive product, and fixing object to obtain an evaluation sample. A schematic diagram of the evaluation sample is shown in FIG. 8A. As shown in Fig. 8A, the double-sided tape and aluminum foil are 50 mm or more long, which is longer than the ABS resin and the adhesive product, and are long enough for the Autograph (registered trademark) gripper to grip the overlapping portion of the evaluation sample where only the double-sided tape and aluminum foil overlap, so that the pull-up strength measurement test described later can be performed. In Fig. 8A (and Fig. 8B and Fig. 8C), 10 represents the stainless steel plate, 11 the adhesive product, 12 the aluminum foil, 13 the double-sided tape, and 14 the ABS resin, respectively.

[0108] Evaluation of adhesive strength of adhesive products (accelerated heat test 1) Thirty evaluation samples were prepared for each of Examples 1 to 3 and Comparative Example 1, and each evaluation sample was placed in a thermo-hygrostat and left to stand for 100 hours under conditions of 40°C and 50% humidity to adjust the condition of each evaluation sample to be uniform.

[0109] After standing, each evaluation sample was further subjected to an accelerated heating test at 40°C. The accelerated heating test was carried out for a maximum of 500 hours, with six evaluation samples being collected at 0 hours, 24 hours, 100 hours, 200 hours, and 500 hours. For half of the collected evaluation samples, a voltage was applied before the pull-up strength was measured. For the remaining half, no voltage was applied before the pull-up strength was measured. The pull-up strength measurement test and application test were carried out as follows.

[0110] (Pulling strength measurement test) For the pull-up strength measurement test, an Autograph (registered trademark) AGS-H manufactured by Shimadzu Corporation was used. A part of the overlapping part of the evaluation sample where only the double-sided tape and the aluminum foil were overlapped was gripped with a gripper and pulled up at a constant speed of 300 mm / min, and the force required to peel the adhesive product (and the object to be fixed) from the adherend was measured (see Figures 8B and C).

[0111] (Applied Test) The voltage application test was performed by attaching electrodes to the evaluation sample so that the conductive adherend side was the positive electrode and the fixed object side was the negative electrode. Using a DC power source and adjusting the voltage with a transformer, a voltage of 30 V was applied to the evaluation sample for 60 seconds.

[0112] The results of the pulling test for each evaluation sample after the accelerated heating test are shown in Tables 1 and 2 below. Table 1 shows the results with voltage application, and Table 2 shows the results without voltage application. The results with voltage application are also shown in Figure 9. The results in the tables and figures show the results of the pulling strength measurement test, and each value is in (N). Each value is the average value of the measured values ​​for three evaluation samples.

[0113] [Table 1]

[0114] [Table 2]

[0115] From Table 1 and Fig. 9, the adhesive product of Comparative Example 1, which does not contain a superabsorbent polymer, shows an increase in pull-up strength after application of voltage after 500 hours. In contrast, the adhesive products of Examples 1 to 3, which contain a superabsorbent polymer, show almost no change in pull-up strength after application of voltage after 500 hours. This shows that the inclusion of a superabsorbent polymer suppresses deterioration of electrical peeling properties due to heat. Furthermore, from Table 2, it is seen that the adhesive properties of each manufactured adhesive product do not deteriorate even after the accelerated heating test.

[0116] Evaluation of adhesive strength of adhesive products (accelerated heat test 2) Twenty-four evaluation samples were prepared for each of Examples 1 and 2 and Comparative Example 1, and an accelerated heating test was performed in the same manner as in Accelerated Heating Test 1, except that the temperature of the accelerated heating test was 80°C. The evaluation samples were collected after 0 hours, 24 hours, 48 ​​hours, and 100 hours, and the pull-up strength was measured.

[0117] The results of the pull-up strength measurement test for each evaluation sample after the accelerated heating test are shown in Tables 3 and 4 below, respectively. Table 3 shows the results with voltage application, and Table 4 shows the results without voltage application. The results with voltage application are also shown in Figure 10. The results in the tables and figures show the results of the pull-up test, and each value is in (N). Each value is the average value of the measured values ​​for three evaluation samples.

[0118] [Table 3]

[0119] [Table 4]

[0120] From Tables 3 and 4 and FIG. 10, the adhesive product of Comparative Example 1, which does not contain a superabsorbent polymer, shows a large increase in pull-up strength after voltage application at 50 hours. The adhesive products of Examples 1 and 2, which contain a superabsorbent polymer, show a suppressed increase in pull-up strength compared to the adhesive product of Comparative Example 1 at any time elapsed. From this, it can be seen that the inclusion of a superabsorbent polymer can suppress the deterioration of electrical peeling properties even when exposed to high heat such as 80°C. Furthermore, from Table 4, it can be seen that the adhesive properties of each adhesive product do not deteriorate even after a severe accelerated heating test such as at 80°C.

[0121] Evaluation of adhesive strength of adhesive products (accelerated heat test 3) For each of the evaluation samples in Example 4 and Comparative Example 1, 24 samples were prepared and subjected to an accelerated heating test in the same manner as in Accelerated Heating Test 1. The evaluation samples at 0 hours, 100 hours, 200 hours, and 500 hours were collected and their pulling strengths were measured.

[0122] The results of the pulling test for each evaluation sample after the accelerated heating test are shown in Tables 5 and 6 below, respectively. Table 5 shows the results with voltage application, and Table 6 shows the results without voltage application. The results with voltage application are also shown in Figure 11. The results in the tables and figures show the results of the pulling test, and each value is in (N). Each value is the average value of the measured values ​​for three evaluation samples.

[0123] [Table 5]

[0124] [Table 6]

[0125] From Table 5 and Fig. 11, the adhesive product of Comparative Example 1, which does not contain a superabsorbent polymer, shows an increase in pull-up strength after application of voltage after 500 hours. On the other hand, the adhesive product of Example 4, which contains a superabsorbent polymer, shows almost no change in pull-up strength after application of voltage after 500 hours. This shows that deterioration of electrical peeling properties can be suppressed even if the type of superabsorbent polymer is changed from that of Examples 1 to 3. Furthermore, from Table 6, it can be seen that the adhesive properties of each adhesive product do not deteriorate even after the accelerated heating test.

[0126] The above experimental results demonstrate that the deterioration of electrical peelability due to heat can be suppressed by producing an electrically peelable adhesive using a highly water-absorbent polymer. [Explanation of symbols]

[0127] 1 Electrically peelable adhesive layer 2. Base material or core material 3. Conductive substrate 4 DC power supply 5. Conductive fixed objects 6 Non-conductive fixed objects 7 Any adhesive 8. Conductive auxiliary materials 9 Non-conductive substrates 10 Stainless steel plate 11 Adhesive products 12 Aluminum foil 13 Double-sided tape 14 ABS resin

Claims

1. An electrically peelable adhesive composition comprising an acrylic polymer, an ionic liquid and a highly water-absorbent polymer.

2. The composition according to claim 1, wherein the highly water-absorbent polymer is selected from sodium poly(meth)acrylate, potassium poly(meth)acrylate, ammonium poly(meth)acrylate, calcium poly(meth)acrylate, magnesium poly(meth)acrylate, hydroxyethyl cellulose, hydroxypropyl cellulose, poly(meth)acrylamide, poly-N-isopropylamide, polyvinylpyrrolidone, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, or derivatives or crosslinked products thereof.

3. 3. The composition according to claim 1, wherein the highly water-absorbent polymer is present in an amount of 1 to 40 parts by weight based on 100 parts by weight of the acrylic polymer.

4. The composition of any one of claims 1 to 3, further comprising a migration enhancer.

5. The composition of claim 4 , wherein the migration enhancer is an alkyl ether of polyethylene glycol.

6. The composition according to claim 5, wherein the alkyl ether of polyethylene glycol is a polyethylene glycol mono(di)methyl ether having a weight average molecular weight of 120 to 360.

7. The composition according to any one of claims 4 to 6, wherein the content of the migration promoter is 5 to 30 parts by weight based on 100 parts by weight of the acrylic polymer.

8. The ionic conductivity of the ionic liquid is 10 -4 ~10 -2 The composition according to any one of claims 1 to 7, wherein the viscosity is S / cm.

9. The composition according to any one of claims 1 to 8, wherein the ionic liquid is represented by the following formula (1): 【Chemistry 1】 [In the formula, R 1 is a divalent hydrocarbon group having 2 to 8 carbon atoms which may contain a heteroatom, and N + Together with R 2 and R 3 are the same or different and are a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (however, when a nitrogen atom forms a double bond with an adjacent carbon atom, R 3 does not exist), X - is Cl - , Br - , I - , AlCl 4 - , Al 2 Cl 7 -, NO 3 - , B.F. 4 - , P.F. 6 - , ClO 4 - , C.H. 3 COO - , C.F. 3 COO - , C.F. 3 SO 3 - , (CF 3 SO 2 ) 2 N - , (FSO 2 ) 2 N - , (CF 3 SO 2 ) 3 C - , AsF 6 - , SbF 6 - , NbF 6 -, F(HF) n - , B(C 6 H 5 ) 4 - , C 4 F 9 SO 3 - , C.F. 3 (CF 2 ) 3 SO 3 - , (CF 3 CF 2 SO 2 ) 2 N - and CF 3 CF 2 COO - is an anion selected from

10. The ionic liquid comprises a cation selected from a pyridinium-based cation, a cyclic aliphatic ammonium cation, and an imidazolium-based cation, and (FSO 2 ) 2 N - , (CF 3 SO 2 ) 2 N - and B.F. 4 - The composition according to any one of claims 1 to 9, which is a salt with an anion selected from the group consisting of:

11. The composition according to any one of claims 1 to 10, wherein the content of the ionic liquid is 5 to 40 parts by weight based on 100 parts by weight of the acrylic polymer.

12. The composition according to any one of claims 1 to 11, wherein the acrylic polymer comprises a copolymer of an alkyl(meth)acrylate having an alkyl group having 1 to 8 carbon atoms, a carboxyl group-containing acrylic monomer, and / or a hydroxyl group-containing acrylic monomer.

13. The composition according to any one of claims 1 to 12, wherein a reduction in pulling strength after leaving the composition at 40°C for 500 hours and applying a voltage thereto is 85% or more, as calculated by the following formula (2): [0010] (wherein α refers to the pull-up strength of an unapplied adhesive product after being left in a space at 40°C for 500 hours; The pull-up strength of an uncharged adhesive product after standing for 500 hours in a space at 40°C refers to a force when an adhesive product in the form of a double-sided tape having an electrically peelable adhesive composition as an adhesive layer is formed, an adherend and an object to be fixed are fixed with the adhesive product, the product is allowed to stand for 500 hours in a space at 40°C, and then the object to be fixed is peeled off from the adherend using a tensile tester. β refers to the pull-up strength of the adhesive product after it is left in a 40℃ space for 500 hours and a voltage is applied. The pull-up strength of an adhesive product after leaving it in a space at 40°C for 500 hours and applying a voltage refers to the force when the adherend and the object to be fixed are fixed with the adhesive product, left in a space at 40°C for 500 hours, a voltage of 30V is applied to the adhesive product for 60 seconds, and then the object to be fixed is peeled off from the adherend using a tensile tester.

14. The composition according to any one of claims 1 to 13, wherein a reduction in pulling strength after leaving the composition at 80°C for 100 hours and applying a voltage thereto is 20% or more, as calculated by the following formula (3): [0025] (wherein α refers to the pull-up strength of an unapplied adhesive product after being left in a space at 80°C for 100 hours; The pull-up strength of an uncharged adhesive product after standing in a space at 80°C for 100 hours refers to a force when an adhesive product in the form of a double-sided tape having an electrically peelable adhesive composition as an adhesive layer is formed, an adherend and an object to be fixed are fixed with the adhesive product, the product is stood in a space at 80°C for 100 hours, and then the object to be fixed is peeled off from the adherend using a tensile tester. β refers to the pull-up strength of the adhesive product after it is left in a space at 80°C for 100 hours and voltage is applied. The pull-up strength of an adhesive product after leaving it in a space at 80°C for 100 hours and applying a voltage refers to the force when the adherend and the object to be fixed are fixed with the adhesive product, left in a space at 80°C for 100 hours, a voltage of 30V is applied to the adhesive product for 60 seconds, and then the object to be fixed is peeled off from the adherend using a tensile tester.

15. The composition according to any one of claims 1 to 14, which is reusable.

16. 16. An electrically peelable adhesive product comprising a substrate and an electrically peelable adhesive layer formed in contact with the substrate, the electrically peelable adhesive layer comprising the electrically peelable adhesive composition according to any one of claims 1 to 15.

17. An electrically peelable adhesive product comprising a core material and two electrically peelable adhesive layers formed so as to be in contact with both sides of the core material, the electrically peelable adhesive layers comprising the electrically peelable adhesive composition according to any one of claims 1 to 15.

18. The adhesive product according to claim 17, which is an adhesive tape or an adhesive sheet.

19. The adhesive product according to any one of claims 16 to 18, which is reusable.

20. A method for peeling an electrically peelable adhesive product, comprising attaching the adhesive product according to any one of claims 16 to 19 to a conductive object so that the adhesive layer is in contact with the conductive object, and then applying a voltage of 30 V or less to the adhesive layer via the conductive object, thereby peeling the adhesive product from the conductive object to which it is directly attached, wherein the conductive object is any one of a conductive adherend, a conductive auxiliary material, or a conductive object to be fixed.

Citation Information

Patent Citations

  • Adhesive and method for producing the same

    JP2004162070A

  • Electrically peelable adhesive composition, electrically peelable adhesive product and method for peeling the same

    JP2010037354A

  • Electrically peelable adhesive composition, electrically peelable adhesive product and method for peeling the same

    JP2010037355A

  • Electrically peelable adhesive composition, electrically peelable adhesive product, and method for peeling product

    US20220195259A1

  • Adhesive composition, adhesive sheet and bonded body

    WO2020050169A1